COLLABORATIVE WORK IN THE PREWRITING STAGE - Wijaya, Juliana (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
This paper explores the notion of collaborative work in the prewriting stage. Several collaborative prewriting activities are presented to encourage students to optimize their peers' help in obtaining ideas to write. Those activities will ultimately help students get interesting ideas to write and develop them into dynamic writing.